Shia Faction Involvement in the Israel-Palestine Conflict: Sunni Responses through the Lens of Religious Moderation - Abdillah, Muhammad Torieq; Wahid, Gusriawan Sholehudin; Alma'arif, Alma'arif (Universitas Nahdlatul Ulama Surabaya, 2025)
This article examines the Israel-Palestine conflict, which has persisted since the is- suance of the Balfour Declaration in 1917. The declaration paved the way for the establishment of Israel in 1948 and consequently led to the displacement of the Pales- tinian population. Since then, numerous confrontations have occurred, including the Six-Day War, the Intifada movements, and repeated assaults on Gaza. The conflict reached a new level of escalation in October 2023 through the Taufan al-Aqsa (Al- Aqsa Storm) operation, involving Hamas with the support of Hezbollah (Lebanon), the Houthi movement (Yemen), and Iran. Although Sunni and Shia groups differ ide- ologically, the participation of Shia factions demonstrates a shared opposition to Israel and a unified front in defending Palestine amidst the complex geopolitical tensions of the Middle East. The findings of this article indicate that the involvement of Shia factions in the Taufan al-Aqsa conflict, such as Iran’s support through Hezbollah and the Houthi movement has effectively created a proxy war against Israel, encompassing both military and ideological dimensions. Despite theological differences, Sunni and Shia actors remain united in resisting Israeli occupation. Within the framework of re- ligious moderation, the principles of tawassuth (moderation) and tasamuh (tolerance) enable Sunnis to support the Palestinian cause on humanitarian grounds, without nec- essarily endorsing Shia doctrinal positions. Solidarity rooted in shared human values thus serves as the foundation for cross-sectarian collaboration in the ongoing Pales- tinian struggle.